تطبيق طريقة المشاورة فى تعليم كتاب العمريطي لترقية مهارة القراءة في المعهد هداي سوكافور ديوك جومبانج - Murtadho, Aceng Ali; Niswah, Isniayatun (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
This research aims to describe the application of the deliberation method in the learning of the Kitab Al-'Imrithi to improve reading skills at the Hudaya Sukapuro Diwek Jombang Islamic boarding school. The background of this research is based on the importance of reading skills as one of the main competencies in Arabic language learning, especially in understanding the yellow book which is rich in nahwu rules. The Kitab Al-'Imrithi was chosen because it is one of the important references in mastering nahwu science in the pesantren environment, while the deliberation method was chosen because of its interactive and participatory characteristics, allowing students to discuss, express opinions, and give feedback under the guidance of teachers or kyai. This research uses a qualitative approach with a case study type, data collection techniques include observation, interviews, and documentation. The collected data focuses on the process of applying the deliberation method and its impact on improving students' reading skills in understanding the contents of the Kitab Al-'Imrithi.